Beacon-based train seat alert system for pregnant travellers / Fatin Nabila Ramli - Ramli, Fatin Nabila (2019)
Some pregnant travellers might not feel comfortable with asking for seat directly to a passenger that seating in the priority seat. Other passengers that seating in the priority seats might not notice towards their surroundings as they are too immersed playing with their smartphones. There are small numbers of passengers that lack of courtesy and they tend to ignore those who has privileges by sleeping. Due to that, this project is to design a device that effortlessly help the pregnant woman to get a seat in the train. Next, this project is to develop a device that can alert the passenger that is seating in the priority seat to give up the seat. Moreover, this project is to test the functionality of the device so that it will alert other passengers. The project development will include sensor-based technology and management system. Beacon will be use in this project as the sensor-based device and a management system will be developed to organize the process of applying for the device using Bootstrap framework. It is expected that by the end of this project a prototype of a sensor-based train seat for pregnant travellers using beacon will be developed.